2019
DOI: 10.1016/j.envres.2019.108572
|View full text |Cite
|
Sign up to set email alerts
|

On-road emissions of passenger cars beyond the boundary conditions of the real-driving emissions test

Abstract: Passenger cars are an important source of air pollution, especially in urban areas. Recently, real-driving emissions (RDE) test procedures have been introduced in the EU aiming to evaluate nitrogen oxides (NOx) and particulate number (PN) emissions from passenger cars during on-road operation. Although RDE accounts for a large variety of real-world driving, it excludes certain driving situations by setting boundary conditions (e.g., in relation to altitude, temperature or dynamic driving). The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 53 publications
3
41
0
Order By: Relevance
“…CO emissions were found to be higher for the more dynamic Downtown SD route compared to the Downtown LA route, due to more transition engine operating conditions and higher loads that favor rich air-fuel mixtures. Similarly, Demuynck et al (2017) and Suarez-Bertoa et al (2019) reported higher real-world CO emissions over more dynamic routes. Results reported here indicate the effects from rich engine operation during uphill/downhill and high-speed driving conditions for the Downtown SD route compared to the flat road Downtown LA route.…”
Section: Gaseous Emissionsmentioning
confidence: 88%
“…CO emissions were found to be higher for the more dynamic Downtown SD route compared to the Downtown LA route, due to more transition engine operating conditions and higher loads that favor rich air-fuel mixtures. Similarly, Demuynck et al (2017) and Suarez-Bertoa et al (2019) reported higher real-world CO emissions over more dynamic routes. Results reported here indicate the effects from rich engine operation during uphill/downhill and high-speed driving conditions for the Downtown SD route compared to the flat road Downtown LA route.…”
Section: Gaseous Emissionsmentioning
confidence: 88%
“…This suggests that gasoline vehicles equipped with TWC can result in high emissions of CO not only during cold start but also after catalyst light-off. High CO emissions from gasoline vehicles during dynamic driving have recently been reported during on-road and on-dyno RDE tests [52,53]. Moreover, Kelly and Groblicki already reported this operation in the U.S. in 1993 [54].…”
Section: On-road Emissions From the Gasoline Vehiclesmentioning
confidence: 90%
“…Diesel L-category as well as dual fuel heavy-duty vehicles are excluded. As a help to the eyes, 1% is represented with a red circle system (higher urea injection flow, more frequent LNT/ NSC regeneration) so that diesel light-duty vehicles will be able to comply with the more stringent NOx standards [52,55,65]. In such context and without setting a standard on the tailpipe N 2 O emissions from diesel LDV and HDV vehicles, the regulation defined to reduce GHG emissions from on-road transportation will have lower impact on climate change mitigation.…”
Section: Trend Along With Emission Standardsmentioning
confidence: 99%